HUKUM DEKONTRUKSI PARIWISATA BUDAYA BALI: ANTARA KEARIFAN LOKAL DAN KOMERSIAL - Purnama Santhi, Ni Nyoman Putri; Cantika, Anak Agung Linda (Kerta Dyatmika, 2024)
The development of globalization and modernization has posed significant challenges for the island of Bali, particularly in maintaining a balance between the preservation of local wisdom and the pressures of commercialization within the cultural tourism sector. This phenomenon has raised concerns over the potential exploitation of local cultural values for economic gain. From a legal perspective, a deconstructive legal approach is required as an evaluative effort toward the legal substance related to local wisdom and the commercialization of Balinese cultural tourism. The objective of this research is to examine and recommend revisions to the existing regulations in order to curb the flow of commercialization and to safeguard local cultural values. This study employs a normative legal research method, utilizing statutory approaches, legal literature, scholarly journals, and other relevant articles. The findings indicate that a deconstructive legal approach may serve as an effective alternative solution in addressing the commercialization of Balinese cultural tourism, through the identification and critical reasoning of the prevailing legal regulations.